2023
DOI: 10.1186/s40795-023-00693-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and associated factors among adolescent girls in Nifas Silk Laphto sub city, Addis Ababa, Ethiopia, 2021

Abstract: Background Addressing the nutritional problems of adolescent girls is important as their nutritional status has a negative effect on the future generation. However, the evidence revealed the variation and unrelated data on the prevalence of dietary diversity and lack of including all adolescent age and community groups in Ethiopia. Hence, this study assessed dietary diversity and associated factors among adolescent girls in Nifas Silk Laphto Sub-city, Addis Ababa Ethiopia, 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Across all age groups, the highest DDS tertile showed a statistically significant higher fiber intake, fruit and vegetable intake, as well as lower ultra-processed foods consumption. Additionally, our finding that higher DDS was associated with higher HDAS and meal frequency is consistent with previous research on adolescents and adults [47][48][49]. The positive association between dietary diversity and meal frequency could be explained, at least in part, by the fact that consuming more meals per day increases the opportunities to include a wider variety of foods per se.…”
Section: Discussionsupporting
confidence: 92%
“…Across all age groups, the highest DDS tertile showed a statistically significant higher fiber intake, fruit and vegetable intake, as well as lower ultra-processed foods consumption. Additionally, our finding that higher DDS was associated with higher HDAS and meal frequency is consistent with previous research on adolescents and adults [47][48][49]. The positive association between dietary diversity and meal frequency could be explained, at least in part, by the fact that consuming more meals per day increases the opportunities to include a wider variety of foods per se.…”
Section: Discussionsupporting
confidence: 92%
“…Our subgroup analysis, on the other hand, showed that the intervention worked better among older and current urban resident participants. There are studies that compliment this study that socio-demographic factors are important predictors of dietary behavior [ 28 , 55 ]. This seems obvious that older adolescents and urban residents can better understand the intervention messages, and have the freedom, authority and confidence to prepare and consume quality food due to mainly their relative access to health information [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary quality can be in uenced by family size and household food production, which can affect the availability and accessibility of food within the household (8, 10). Nutritional knowledge is an essential determinant of diet quality, as individuals who know the nutritional value of various foods are better equipped to make informed dietary choices that support good health (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%